1999
DOI: 10.1177/030802269906200707
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Palliative Care: The Attitudes of Occupational Therapists

Abstract: The attitudes of 44 occupational therapists on the place of spirituality within palliative care were investigated. Their responses to a postal questionnaire indicated that spirituality was an important part of life for 35 (80%) respondents, helped 33 (75%) respondents with daily job responsibilities and was viewed as an important dimension of health and rehabilitation by 39 (89%) respondents. Spiritual issues were considered to be within the scope of occupational therapy by 33 (75%) respondents. However, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 21 publications
7
63
0
1
Order By: Relevance
“…Mthembu et al (2014) and Rose (1999) found that spiritual care is unique to every individual with relationship with God, nature and other, which is in good agreement with the results of the present study. However, the participants in the study had low mean value of holistic approach, and as a result, this finding is consistent with other previous studies (Tiew et al 2013b).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mthembu et al (2014) and Rose (1999) found that spiritual care is unique to every individual with relationship with God, nature and other, which is in good agreement with the results of the present study. However, the participants in the study had low mean value of holistic approach, and as a result, this finding is consistent with other previous studies (Tiew et al 2013b).…”
Section: Discussionsupporting
confidence: 92%
“…Less than half of the participants indicated that team approach is very important in addressing spiritual care. The finding is consistent with findings of past studies by Tiew and Drury (2012) and Rose (1999) which recommended that a multidisciplinary approach should be implemented to address the spiritual needs of clients. One of the issues that emerge from these findings is the involvement of all members in addressing the role of spirituality in health care in an interdisciplinary team.…”
Section: Discussionsupporting
confidence: 91%
“…2;Mayers and Johnston 2008;Miller and Thoresen 2003;Ross 2006;Swinton 2012). Other studies have also included a definition for the same reason (Collins et al 2001;Farrar 2001;Rose 1999) or have recommended the use of definitions (Engquist et al 1997;Johnston and Mayers 2005). The following definitions were used here: Spirituality:…”
Section: Definitionsmentioning
confidence: 99%
“…Lawrence et al 2007;McSherry and Jamieson 2011;Rose 1999). These issues were separated into two questions, based on literature showing that the terms are used differently (Engquist et al 1997;Farrar 2001;Johnston and Mayers 2005;Koenig 2008a) although there may be some overlap (Hill and Pargament 2003;Koenig 2008a;Miller and Thoresen 2003).…”
Section: Definitionsmentioning
confidence: 99%
“…There is a strong tendency among those in the helping professions to believe that a patient's spirituality/religiousness influences the course of medical and psychological interventions, recuperation from chronic illness, and mortality (Feher and Maley 1999;Kirkpatrick and McCullough 1999;Rose 1999;McCullough et al 2000). In the literature on chemical dependence, spirituality and religiousness have been Int…”
Section: Spiritual and Religious Factors In Health Interventionmentioning
confidence: 99%